Integrated management of processes and information - Shaw, Kenneth A. (Kenneth Alan), 1941- (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2013)
Each step in a company's manufacturing, service, and information processes uses, creates, supplies, and stores information. In many businesses, the information processes are managed separately from other business processes. However, they should be considered together with other operations in a process to develop more effective and less-expensive methods for acquiring and using that information. Using a conversational tone, the author discusses a number of the procedural and managerial policy considerations for small and large businesses regarding information technology, process management, and business choices. The discussion focuses more on informing the reader about process-oriented concepts and management options available rather than providing specific recommendations regarding which process or information strategy to use.
Contents -- List of illustrations -- Preface -- Acknowledgments -- Introduction -- 1. Changing role of processes and information -- 2. Nature of information -- 3. Modeling integrated information and processes -- 4. Use and acquisition of information -- 5. Alphabet soup, big data, cloud computing, DSS, ERP, VoIP -- 6. Managerial considerations -- Appendix A. Glossary -- Appendix B. Acronym and symbol definitions -- Appendix C. Excel tips and useful functions -- Notes -- References and bibliography -- Index.
Part of: 2013 digital library.
Includes bibliographical references (pages 171-176) and index.
Title from PDF title page (viewed on November 5, 2013).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Business information services; Information resources management; Decision support systems; Management information systems; information processes; service processes; manufacturing processes; process management; information technology; enterprise software solutions; stochastic data; deterministic data; service blueprint; block diagram; cross- functional diagram; information flow; information transfer; information standardization; information medium; cyber security; value-added step; dematerialization; food service information processes; DSS; ERP; MRP; CRM; SPC; PDM; SaaS; Big Data; data mining; SMB; decision support systems; business intelligence; Shannon theory of communication; cloud computing; BYOD; VoIP; barcode; OCR; RFID; inventory tracking; Electronic books